Comparison of Outcomes of Methylprednisolone With Serratiopeptidase in Reducing Postoperative Complications After Extraction of the Mandibular Third Molar - Ghauri, Bushra; Rahim, Muhammad; Khan, Muhammad Azad; Kanwal, Sana; Razzaq, Zeenat; Zarak Khan, Arbab (Biological and Clinical Sciences Research Journal, 2025)
Surgical extraction of impacted mandibular third molars is one of the most common oral and maxillofacial procedures and is frequently associated with postoperative pain, swelling, and limitation of mouth opening. Pharmacological agents such as corticosteroids and proteolytic enzymes are widely prescribed to minimize these complications; however, comparative evidence on their efficacy remains limited. Objective: To compare the effectiveness of methylprednisolone and serratiopeptidase in reducing postoperative pain, swelling, and trismus following surgical extraction of impacted mandibular third molars. Methods: A randomized controlled trial was conducted at the Department of Oral and Maxillofacial Surgery, Sandeman Provincial Hospital, Quetta, Pakistan, from December 2021 to June 2022. Ninety-six eligible patients were randomly allocated into two equal groups. Group A received oral methylprednisolone 4 mg every 8 hours, and Group B received oral serratiopeptidase 10 mg every 12 hours for five days postoperatively. Pain was assessed using a visual analogue scale, swelling was measured using standardized anatomical landmarks, and mouth opening was recorded using interincisal distance. Data were analyzed using SPSS version 23, with p ≤ 0.05 considered statistically significant. Results: Both groups were comparable in age, gender distribution, impaction side, and impaction classification. Methylprednisolone demonstrated significantly lower postoperative pain (1.3 ± 0.32 vs 7.3 ± 2.0, p < 0.001) and greater improvement in mouth opening (1.3 ± 2.5 vs 7.2 ± 4.1, p < 0.001) than serratiopeptidase. Serratiopeptidase showed relatively better reduction in postoperative swelling (p = 0.04). Similar outcome trends were observed among participants aged 23–30 years. Conclusion: Methylprednisolone was more effective in reducing postoperative pain and trismus, whereas serratiopeptidase provided superior reduction in swelling following third molar surgery. The predominant clinical requirement may guide the selection of either medication. Both agents appear safe and beneficial when used short-term in postoperative management.